Polyadenylation of Sine Transcripts Generated by RNA Polymerase III Dramatically Prolongs Their Lifetime in Cells - Ustyantsev, I. G.; Tatosyan, K. A.; Stasenko, D. V.; Kochanova, N. Y.; Borodulina, O. R.; Kramerov, D. A. (Molecular biology (New York), 2020)
— Short Interspersed Elements (SINEs) are mobile genetic elements of higher eukaryotes, which originated during evolution from various tRNAs and less often from 5S rRNA and 7SL RNA. Similar to the genes of these RNAs, SINEs are transcribed by RNA polymerase III. The transcripts of some mammalian SINEs have an ability to undergo AAUAAA-dependent polyadenylation, which is unique for the RNA polymerase III transcripts. It is well known that this polyadenylation of many RNA polymerase II transcripts (e.g., mRNAs) increases their lifetime in the cell. The aim of this work is to examine whether the stability of SINE transcripts increases as a result of AAUAAA-dependent polyadenylation. HeLa cells were transfected with SINE DNA, both containing and not containing the polyadenylation signal (AATAAA). One day later, the transcription was inhibited by actinomycin D, and the decrease in the level of the SINE transcripts was monitored by northern hybridization. For all the eight studied SINEs, the half-life of nonpolyadenylated transcripts was 20–30 minutes, and for polyadenylated transcripts, this parameter exceeded 3 hours. Interestingly, the insertion of an additional 80-bp DNA fragment into the middle region of B2 SINE did not significantly reduce the stability of the polyadenylated transcripts. It is most likely that the increase in the lifetime of the polyadenylated SINE transcripts is due to the fact that the poly(A) tail interacts with the poly(A)-binding proteins (PABPs), thus protecting the RNA from degradation by the exonucleases acting from the 3'-end. The results make it possible to design SINE-based vectors intended for the expression of short noncoding RNAs, which are stable in a cell due to polyadenylation.